Characteristics of preliminary breakdown pulses in positive ground flashes during summer thunderstorms in Sweden - Johari, Dalina; Ismail, Mohd Muzafar; Cooray, Vernon; Rahman, Mahbubur; Hettiarachchi, Pasan (MDPI AG, 2016)
This paper presents the characteristics of the preliminary breakdown pulses (PBP) in 51 positive ground flashes recorded during 2014 summer thunderstorms in Sweden. Electric field measurements were conducted remotely using a broadband antenna system (up to 100 MHz) for a recording length of 1 s with 200 ms trigger time. In the analysis, PBP trains were observed in 86% of the cases. Based on the number of trains preceding the first return stroke, the PBP were classified into single and multiple train PBP. Characteristics of the first PBP train were determined and based on the initial polarity of the pulses, three types of PBP were identified. Characteristics of the subsequent PBP trains in the multiple train PBP were also analyzed and they were compared with the first PBP train. Based on the conceptual charge cloud configuration, we found that the inverted dipole is consistent with our observation. We also found that PBP in positive ground flashes during summer thunderstorms in Sweden are weak since the average ratios of the PBP peak to the first return stroke peak lie only between 0.21 and 0.26. Possible reasons for no detection of PBP and the different types of PBP observed were also discussed.